High‐Throughput Combinatorial Optimizations of Perovskite Light‐Emitting Diodes Based on All‐Vacuum Deposition. (8th October 2019) - Li, Jinghui; Du, Peipei; Li, Shunran; Liu, Jing; Zhu, Menghua; Tan, Zhifang; Hu, Manchen; Luo, Jiajun; Guo, Deqiang; Ma, Lin; Nie, Zhaogang; Ma, Ying; et al.
Abstract: Light‐emitting diodes (LEDs) based on lead halide perovskites demonstrate outstanding optoelectronic properties and are strong competitors for display and lighting applications. While previous halide perovskite LEDs are mainly produced via solution processing, here an all‐vacuum processing method is employed to construct CsPbBr3 LEDs because vacuum processing exhibits high reliability and easy integration with existing OLED facilities for mass production. The high‐throughput combinatorial strategies are further adopted to study perovskite composition, annealing temperature, and functional layer thickness, thus significantly speeding up the optimization process. The best rigid device shows a current efficiency (CE) of 4.8 cd A −1 (EQE of 1.45%) at 2358 cd m −2, and best flexible device shows a CE of 4.16 cd A −1 (EQE of 1.37%) at 2012 cd m −2 with good bending tolerance. Moreover, by choosing NiO x as the hole‐injection layer, the CE is improved to 10.15 cd A −1 and EQE is improved to a record of 3.26% for perovskite LEDs produced by vacuum deposition. The time efficient combinatorial approaches can also be applied to optimize other perovskite LEDs. Abstract : Upon all‐vacuum deposition, highly repeatable perovskite light‐emitting diodes are demonstrated. In addition, high‐throughput combinatorial strategies are applied to accelerate the device's optimization. After a series of combinatorial optimizations, the champion device shows the best reported performance thus far (current efficiency of 10.15 cd A −1, external quantum efficiency of 3.26%) among the devices produced by vacuum processes.